Efek F100 dan formula tepung tempe terhadap kadar serum Fe dan hemoglobin pada anak gizi kurang - Tsalissavrina Iva; Endy Paryanto Prawirohartono; Lily Arsanti Lestari (Jurnal Gizi Klinik Indonesia, 2012)
Background: Protein energy deficiency is a major public health problem in Indonesia. WHO has recommended F100 made from skim milk for undernourished patient. Alternative formulas have been developed using other nutritious foods that are cheaper, easily accessible and can be used for children with lactose intolerance such as tempe flour.Objective: To investigate the effect of F100 and tempe flour formula supplementation on serum Fe and hemoglobin (Hb) levels of undernourished child.Method: This was an experimental study with randomized controlled clinical trial design and purposive sampling method. Subjects of the study were undernourished patients aged 1-10 years hospitalized at Dr. Saiful Anwar Hospital Malang. Sample consisted of 30 patients divided into 2 groups; group 1 supplemented with F100 and group 2 with tempe flour formula. Hb level was assessed by cyanmethemoglobin and serum Fe level by colorimetric method. Dietary intake data was collected by visual comstock and food recall. Data were analyzed by chi square, unpaired t-test and double linear regression.Results: Statistical analysis showed that there were no significant differences in Hb (p=0.139) and serum Fe levels (p=0.313) between both groups after treatment. Intake data indicated that there was a significant disparity in protein (p=0.019) and Fe intake (p=0.006) between the two groups, whereas energy, fat and carbohydrate intake showed no significant differences. Lastly, the association between energy and nutrient intake with serum Fe and Hb levels was not significant and the correlation was weak (r<1).Conclusion: There were no significant differences in hemoglobin and serum Fe levels between F100 group and tempe flour formula group, but there was a significant difference in protein and Fe intake.